ECONOMIC SUSTAINABILITY – A BASIC FACTOR FOR INCREASING THE QUALITY OF LIFE OF THE POPULATION - Elena TIMOFTI; Veronica MOVILEANU; Aliona ȘARGO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this paper, the authors revealed the concepts of development and economic growth, economic sustainability and quality of life. The authors determined and analyzed in dynamics the period 2010-2018, the trend of changing indicators, development and economic growth at the macroeconomic level such as: the value of Gross Domestic Product (GDP), GDP per capita, and the dynamics of the average monthly nominal salary of an employee per economy, disposable incomes per person, their structure and socio-economic indicators that characterize the quality level of the age of the population in the Republic of Moldova. Although there are modest increases in the number of nominated indicators, the authors consider that there are still a number of issues that need to be addressed, solved and complied with EU and other international standards. The research contains data that will surely be of interest to those concerned with the quality of life of the population. In essence, research in the field of quality of life aims at creating a complex image of quality of life, by analyzing different components of population’s life. The following research procedures and methods have been applied in the research process: observation method, comparison, graphical method, table method, chronological series method, etc.